Double dielectric barrier discharge incorporated with CeO2-Co3O4/γ-Al2O3 catalyst for toluene abatement by a sequential adsorption–discharge plasma catalytic process. (15th March 2022) - Li, Shijie; Yu, Xin; Dang, Xiaoqing; Wang, Pengyong; Meng, Xiangkang; Wang, Qi; Hou, Hao
Abstract: As a promising technique to remove volatile organic compounds (VOCs), non-thermal plasma (NTP) has been paid much attention recently. However, the practical implementation of NTP is limited owing to its disadvantages such as low mineralization rate, unsatisfactory energy efficiency and the generation of multiple byproducts. Reactor configuration optimization and plasma coupled catalysis are the two alternatives to improve the efficiency of NTP. A packed bed double dielectric barrier discharge (DDBD) system was established and the performance of CeO2 -Co3 O4 catalysts for toluene abatement was evaluated in a sequential process. It was found that complete toluene removal could be achieved in the DDBD reactor packed with different catalysts. Among them, CeO2 -Co3 O4 binary catalysts showed higher toluene degradation performance than monometallic samples and Ce1Co3 had the best mineralization rate (89.68%) and energy yield (3.04 g/kWh). The effects of Ce/Co ratio on the structural and redox characteristics of the samples were analyzed by BET, XRD, TEM, XPS and H2 -TPR. The superior catalytic activity was attributed to the interplay between Ce and Co species, which created abundant defects and oxygen vacancies and improved the concentration of surface adsorbed oxygen and the reducibility of catalyst. The effects of the relative parameters, such as applied voltage, toluene adsorbed amount and discharge time on the toluene degradation efficiency were also explored. Finally, the toluene decomposition mechanism in the DDBD catalytic system was speculated according to the detected organic products. The findings in this work can provide vital insight in plasma catalytic degradation of VOCs by sequential process. Graphical abstract: Graphical abstract illustration: For the DDBD catalytic reactor, CeO2 -Co3 O4/γ-Al2 O3 catalysts and ZSM-5 zeolite were packed in the inner tube and outer tube, respectively. During adsorption and discharge stage, the toluene containing gas and pure air entered the reactor from the inner tube and exited from the outer tube. After the plasma was turned on, most of the toluene adsorbed on the supported catalysts in the inner tube was degraded and oxidized into COx through heterogeneous catalytic reaction on the catalysts surface. Part of the toluene was desorbed during discharge and entered the outer tube, and was directly degraded in the gas phase or adsorbed by ZSM-5. Subsequentially, the secondary adsorbed toluene was gradually degraded on the surface of ZSM-5. Image 1 Highlights: ● CeO2 -Co3 O4 catalysts was prepared for toluene oxidation in a novel DDBD reactor ● The interaction between Ce and Co enhanced the redox ability and content of Oads ● Ce1Co3 had the best toluene oxidation performance due to its superior redox ability ● Plausible adsorbed toluene degradation mechanism in plasma catalysis was proposed